2013
DOI: 10.1063/1.4825099
|View full text |Cite
|
Sign up to set email alerts
|

Multivalent ion effects on electrostatic stability of virus-like nano-shells

Abstract: Electrostatic properties and stability of charged virus-like nano-shells are examined in ionic solutions with monovalent and multivalent ions. A theoretical model based on a thin charged spherical shell and multivalent ions within the "dressed multivalent ion" approximation, yielding their distribution across the shell and the corresponding electrostatic (osmotic) pressure acting on the shell, is compared with extensive implicit Monte-Carlo simulations. It is found to be accurate for positive or low negative s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 50 publications
1
38
0
1
Order By: Relevance
“…In these situations, one deals with a difficult problem in which neither the WC nor the SC limiting laws can be applied without reservations. For such asymmetric Coulomb fluids, a generalized dressed multivalent-ion approach, that bridges the two limits in one single theoretical framework, has been introduced [7,34] and tested against extensive explicit-and implicition simulations [7,[34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…In these situations, one deals with a difficult problem in which neither the WC nor the SC limiting laws can be applied without reservations. For such asymmetric Coulomb fluids, a generalized dressed multivalent-ion approach, that bridges the two limits in one single theoretical framework, has been introduced [7,34] and tested against extensive explicit-and implicition simulations [7,[34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Siber and Podgornik showed that the filled ssRNA virions exhibit a small residual negative osmotic pressure, which depends strongly on the amount of capsid charges and can be turned positive with relatively higher capsid charge [28]. In addition, Javidpour et al studied the effects of multivalent ions, which can fundamentally change the nature of electrostatic interactions [38], on the osmotic pressure and the stability of the virus like empty shells, showing that the multivalent ions can turn a positive electrostatic osmotic pressure into a negative one [36]. Furthermore, recent all atom molecular dynamics simulations showed that the osmotic pressure inside an empty Poliovirus capsid is negative, suggesting that the mechanism might be connected with excess charges on the capsid that prevent the solution ion to exchange with the capsid [37], a scenario at odds with what we know about the permeability of capsids.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several theoretical studies that investigate the osmotic pressure of ssRNA viruses [28,31,[35][36][37]. Siber and Podgornik showed that the filled ssRNA virions exhibit a small residual negative osmotic pressure, which depends strongly on the amount of capsid charges and can be turned positive with relatively higher capsid charge [28].…”
Section: Introductionmentioning
confidence: 99%
“…[7, 81, 99-104, 106-108, 112-119] and references therein), or more generally, the dressed multivalent-ion theory [27,103,120,121], which provides a very good approximation for the study of asymmetric Coulomb fluids over a wide range of parameters as verified by explicit-ion and implicit-ion simulations. The dressed multivalent-ion theory reproduces the mean-field Debye-Hückel theory and the standard strong-coupling theory for counterion-only systems [99-103, 106-108, 112-118] as two limiting theories in the regime of large and small Debye screening lengths and, therefore, bridges the gap between these two limits [27,103,[120][121][122][123]. The key step in this latter approach is to integrate out the degrees of freedom associated with monovalent ions by means of a linearization approximation, justified only for highly asymmetric Coulomb fluids q ≫ 1, and yielding an effective Debye-Hückel (DH) interaction between the remaining multivalent ions and the surface charges (if any) [120].…”
Section: A Formal Backgroundmentioning
confidence: 78%